Peralatan Keselamatan Kerja Pada Perahu Slerek di PPN Pengambengan, Kabupaten Jembrana, Bali - Santara, Adi Guna; Purwangka, Fis; Iskandar, Budhi Hascaryo (Jurnal IPTEKS Pemanfaatan Sumberdaya Perikanan, 2014)
Fishing is one of the most challenging activities in the world. It is about 80% of ship accidents due to human error. The availability and proper use of safety equipment can minimize the risk. This study aims to identify the suitability of safety equipment used on Slerek boat in PPN Pengambengan, Bali in accordance with international and national standards, and describes the role of relevant institutions to increase the fishermen safety. In this study, we used a survey method, in which focussed on three main aspects includingÂ the types of safety equipment, numbers of safety equipment, and the suitability of equipment which must be taken. The lack of equipment and awareness about safety, and do not comply with the national standards for boat less than 24 meters length will directly affect the fishermen safety. The lack of regulations on the small boat safety showed that the fishermen safety in fishing activities in Indonesia have not been considered and there is no clear policy from local and central government.Â Â